Natural antioxidant pterostilbene as an effective antibiofilm agent, particularly for gram-positive cocci - Vaňková, E; Paldrychová, M; Kašparová, P; Lokočová, K; Kodeš, Z; Maťátková, O; Kolouchová, I; Masák, J (World journal of microbiology & biotechnology, 2020)
Pterostilbene (PTE), a dimethylated analogue of resveratrol, mostly contained in Vitis vinifera leaves or in other plant sources is well-known for its antioxidant activity. Due to its bioavailability, low hydrophilicity and thus ability to penetrate hydrophobic biological membranes it was found to be an antimicrobial agent. These properties of PTE offer the possibility of its use in the treatment of microbial infections. The emergence of antibiotic resistance of microorganisms is often caused by their ability to form biofilm; new substances with antibiofilm activity are therefore sought. The representatives of opportunistic pathogenic gram-positive and gram-negative bacteria as well as fungi were used for the determination of minimum inhibitory concentrations (MIC50 and MIC80), minimum biofilm inhibitory concentrations (MBIC50 and MBIC80) and minimum biofilm eradication concentrations (MBEC50 and MBEC80) of PTE and commonly used antibiotics erythromycin, polymyxin B or antimycotic amphotericin B. Total biofilm biomass was investigated by crystal violet staining, and the results were confirmed using microscopic techniques. The most significant antibiofilm action was proved for gram-positive cocci, e.g., MBEC50 of PTE for all strains of Staphylococcus epidermidis tested was 25 mg/L. By contrast, the antibiotic ERM did not exhibit antibiofilm activity in most cases. The permeabilization of cell membranes of gram-positive cocci biofilm by MBIC50 and MBEC50 of PTE was confirmed by LIVE/DEAD staining using spinning disc confocal microscopy. PTE significantly influenced the ability of gram-positive cocci to form biofilm and it effectively eradicated pre-formed biofilm in vitro; its potential for the treatment of biofilm-associated infections of Staphylococcus spp. or Enterococcus faecalis is thus apparent.
Keywords: Vitis; stilbeny; Gram-Positive Bacteria; Gram-positive cocci; gramnegativní bakterie; Pterostilbene; Pseudomonas aeruginosa; antibakteriální látky; Stilbenes; Enterococcus faecalis; Biofilm inhibition; Plant Leaves; Anti-Bacterial Agents; rostlinné extrakty; grampozitivní koky; Microbial Sensitivity Tests; antioxidancia; Eradication; mikrobiální testy citlivosti; biofilmy; Antibiofilm; Biofilms; Gram-Positive Cocci; Staphylococcus epidermidis; Plant Extracts; Gram-Negative Bacteria; listy rostlin; grampozitivní bakterie; Antioxidants